Corrosion-resistant oil-resistant shore power cable sheath material and preparation method thereof

The intermediate is formed by using 2,2-dihydroxymethylpropionic acid, sodium hydroxide and allyl chloride in the shore cable sheath material, and combined with other substances to prepare corrosion-resistant and oil-resistant sheath material. , solves the problem of poor performance of traditional materials in harsh environments and extends the service life of the cable.

CN119264645AActive Publication Date: 2025-01-07JIANGSU ANTOP POLYMER CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411607899.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-07
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

Traditional polyurethane materials are used for shore power cable sheaths. In harsh seaside environments, they are poor in corrosion resistance, oil and water resistance, and cannot protect cables for a long time, resulting in a shortened service life of the cable.

Method used

Using a preparation method of corrosion-resistant oil-resistant cable sheath material, the intermediate is formed by reacting 2,2-dihydroxymethylpropionic acid, sodium hydroxide and allyl chloride, and with dodecanoheptanol, Reacting substances such as methylbenzenesulfonic acid to form modification additives and reinforcers, combined with microcrystalline cellulose and modified resin, it is melt extruded and ultraviolet irradiated to form a sheath with high corrosion resistance, oil resistance and water resistance. Material.

Benefits of technology

It significantly improves the corrosion resistance, oil and water resistance of the shore power cable sheath, extends the service life of the cable, and ensures that it works normally in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant and oil-resistant shore power cable sheath material and a preparation method thereof.The material is prepared from, by weight, 80-100 parts of modified resin, 8-10 parts of a modified additive, 8-10 parts of an enhancer, 5-10 parts of modified cellulose and 2-5 parts of benzoin diethyl etherate.The castor oil is added in the preparation process of the modified resin, so that the modified resin forms a branched structure; the molecular structure contains an organosilicon chain segment, a cyano group, a benzene ring and a long-chain alkyl group, the benzene ring structure has stable pi electron cloud and is not easy to interact with grease molecules, the long-chain alkyl group and the organosilicon chain segment can increase the hydrophobicity of the material and further improve the oil-resistant effect of the material, the cyano group can endow the modified resin with very strong polarity, and the oil-resistant effect is further improved; by adding the modified cellosilk, the integrity of the material can be improved, the diffusion of a corrosive medium is reduced, and meanwhile, the crosslinking density is improved, so that the corrosion-resistant, oil-resistant and water-resistant effects are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cable sheath material preparation, and in particular to a corrosion-resistant and oil-resistant shore power cable sheath material and a preparation method thereof. Background Art

[0002] As economic, trade and cultural exchanges between countries around the world become more frequent, more and more ships are traveling between countries. The ships arriving at the port have caused serious pollution to the environment of the port city, and shore power transmission technology can provide clean energy for ships arriving at the port. In order to meet the requirements of high power and graded loads in the port, high-voltage shore power cables are used for ship-shore interactive power transmission. Shore power cables are laid exposed in the air and are in a humid port, exposed to direct sunlight. Cranes, winding reels and other facilities must be used for connection. During operation, they are affected by sea breeze and tidal shaking. In order to extend the service life of the cable, a layer of sheath material is squeezed on its surface to protect the insulation layer and conductor from the influence of the external environment. The sheath of the shore power cable is usually made of polyurethane material, but the traditional polyurethane material has poor corrosion resistance, oil resistance and water resistance. After a period of use, the sheath will also age and cannot play a role in protecting the cable. Summary of the invention

[0003] The purpose of the present invention is to provide a corrosion-resistant and oil-resistant shore power cable sheath material and a preparation method thereof, so as to solve the problem that the current shore power cable sheath cannot protect the normal operation of the cable for a long time in such a harsh environment as the seaside.

[0004] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a corrosion-resistant and oil-resistant shore power cable sheath material comprises the following steps: Step A1: 2,2-dihydroxymethylpropionic acid, sodium hydroxide and acetone are mixed evenly, and reacted for 1-1.5 hours at a speed of 120-150 r / min and a temperature of 20-25° C., then allyl chloride is added, and the reaction is carried out for 3-5 hours, and the pH is adjusted to be acidic to obtain intermediate 1, and intermediate 1, dodecafluoroheptanol, p-toluenesulfonic acid and toluene are mixed evenly, and reacted for 3-5 hours at a speed of 60-80 r / min and a temperature of 110-120° C. to obtain intermediate 2; Step A2: The intermediate 2, triethoxysilane, chloroplatinic acid and DMF are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 6-8 hours at a speed of 120-150 r / min and a temperature of 90-100° C. to obtain a modified additive; dithioerythritol, dodecyl vinyl ether, benzophenone and DMF are mixed evenly, and the reaction is carried out for 3-5 hours at a speed of 60-80 r / min, a temperature of 20-25° C. and irradiation with 365 nm ultraviolet light; isocyanatepropyl triethoxysilane is added, and the reaction is continued for 2-4 hours to obtain a strengthening agent; Step A3: Mix microcrystalline cellulose and sodium hydroxide solution, react for 1-1.5 hours at a rotation speed of 200-300 r / min and a temperature of 20-25° C., add allyl chloride, and react for 3-5 hours to obtain modified cellulose. Weigh the following raw materials in parts by weight: 80-100 parts of modified resin, 8-10 parts of modified additive, 8-10 parts of reinforcing agent, 5-10 parts of modified cellulose and 2-5 parts of benzoin ethyl ether. Melt and extrude the raw materials at a temperature of 170-180° C., cool and soak in water for 1-1.5 hours, and irradiate under 365 nm ultraviolet light for 8-10 seconds to obtain a corrosion-resistant and oil-resistant shore power cable sheath material.

[0005] Furthermore, the molar ratio of 2,2-dihydroxymethylpropionic acid, sodium hydroxide and allyl chloride in step A1 is 1:3.1:2, the molar ratio of intermediate 1 and dodecafluoroheptanol is 1:1, and the amount of p-toluenesulfonic acid is 1% of the mass of dodecafluoroheptanol.

[0006] Furthermore, the molar ratio of intermediate 2 and triethoxysilane described in step A2 is 1:2, the amount of chloroplatinic acid used is 1‰ of the mass of triethoxysilane, the molar ratio of dithioerythritol, dodecyl vinyl ether and isocyanatepropyltriethoxysilane is 1:2:2, and the amount of benzophenone used is 5‰ of the mass of dodecyl vinyl ether.

[0007] Furthermore, the amount ratio of microcrystalline cellulose, sodium hydroxide solution and allyl chloride described in step A3 is 2g:30mL:3mL, and the mass fraction of sodium hydroxide solution is 5%.

[0008] Further, the modified resin is prepared by the following steps: Step B1: Tetramethylcyclotetrasiloxane, acrylonitrile, chloroplatinic acid and DMF are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 4-6 hours at a speed of 200-300 r / min and a temperature of 75-80° C. to obtain a modifier; octamethylcyclotetrasiloxane, tetramethyltetraphenylcyclotetrasiloxane, a modifier, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 3-5 hours at a speed of 120-150 r / min and a temperature of 105-110° C. to obtain dihydrogenpolysiloxane; Step B2: Dihydrogen polysiloxane, p-hydroxycinnamic acid, chloroplatinic acid and DMF are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 3-5 hours at a speed of 120-150 r / min and a temperature of 80-85° C. to obtain modified polysiloxane; the modified polysiloxane, dodecanol, p-toluenesulfonic acid and toluene are mixed evenly, and the reaction is carried out for 6-8 hours at a speed of 60-80 r / min and a temperature of 110-120° C. to obtain a modified monomer; Step B3: Add polycaprolactone diol into a reaction kettle, introduce nitrogen protection, stir and add diphenylmethane diisocyanate and dibutyltin dilaurate at a speed of 60-80r / min and a temperature of 60-65°C, react for 2-3h, add modified monomer and castor oil, continue to react for 2-3h, cool to 35-40°C, add DMF and KH550, continue to react for 1-1.5h, and dry to obtain a modified resin.

[0009] Furthermore, the molar ratio of tetramethylcyclotetrasiloxane and acrylonitrile described in step B1 is 1:4, the amount of chloroplatinic acid used is 1‰ of the mass of acrylonitrile, and the molar ratio of octamethylcyclotetrasiloxane, tetramethyltetraphenylcyclotetrasiloxane, modifier, tetramethylammonium hydroxide and tetramethyldisiloxane is 1.6:0.4:0.4:3:2.

[0010] Furthermore, the molar ratio of dihydrogenpolysiloxane and p-hydroxycinnamic acid in step B2 is 1:2, the amount of chloroplatinic acid is 1‰ of the mass of p-hydroxycinnamic acid, the molar ratio of modified polysiloxane and dodecanol is 1:2, and the amount of p-toluenesulfonic acid is 2% of the mass of dodecanol.

[0011] Furthermore, the molar ratio of the polycaprolactone diol, diphenylmethane diisocyanate, modified monomer, castor oil and KH550 in step B3 is 4.5:10:3:1.5:1, and the molecular weight of the polycaprolactone diol is 2000.

[0012] The beneficial effects of the present invention are as follows: a corrosion-resistant and oil-resistant shore power cable sheath material prepared by the present invention comprises the following steps: 2,2-dihydroxymethylpropionic acid and sodium hydroxide are reacted to form sodium hydroxyl, sodium hydroxyl is reacted with the chlorine atom site on allyl chloride, and the pH is adjusted to be acidic to obtain intermediate 1, intermediate 1 is reacted with dodecafluoroheptanol to esterify the carboxyl group on intermediate 1 with the hydroxyl group on dodecafluoroheptanol to obtain intermediate 2, intermediate 2 is reacted with triethoxysilane under the action of chloroplatinic acid to graft the double bond on intermediate 2 with the Si-H bond on triethoxysilane to obtain a modified additive, dithioerythritol and dodecyl vinyl ether are reacted under the action of benzophenone under ultraviolet irradiation to make the thiols on dithioerythritol esterify. The double bonds on the base and dodecyl vinyl ether are grafted, and then isocyanate propyl triethoxysilane is added to react the thiol group on isocyanate propyl triethoxysilane with the alcohol hydroxyl group on dithioerythritol to obtain a reinforcing agent, the microcrystalline cellulose is treated with sodium hydroxide to form sodium cellulose, and then reacted with allyl chloride to graft double bonds on the cellulose molecules, the modified resin, the modified additive, the reinforcing agent, the modified cellulose and benzoin ethyl ether are melt-extruded and soaked in cold water, the siloxane on the modified resin, the modified additive and the reinforcing agent molecules is hydrolyzed and condensed, and then under ultraviolet light irradiation, the double bonds on the modified resin, the modified additive, the reinforcing agent and the modified cellulose molecules are cross-linked and grafted to obtain a corrosion-resistant and oil-resistant shore power cable sheath material.

[0013] The modified resin is prepared by reacting tetramethylcyclotetrasiloxane and acrylonitrile under the action of chloroplatinic acid to form a Si-H bond on tetramethylcyclotetrasiloxane and a double bond on acrylonitrile to obtain a modifier, ring-opening octamethylcyclotetrasiloxane, tetramethyltetraphenylcyclotetrasiloxane and the modifier, and then condensing with tetramethyldisiloxane to obtain dihydrogenpolysiloxane, reacting dihydrogenpolysiloxane with p-hydroxycinnamic acid to form a grafted Si-H bond on the dihydrogenpolysiloxane and a double bond on the p-hydroxycinnamic acid to obtain a modified polysiloxane, reacting the modified polysiloxane with dodecanol to form an esterification of a carboxyl group on the modified polysiloxane and a hydroxyl group on the dodecanol to obtain a modified monomer, reacting polycaprolactone diol with diphenylmethane diisocyanate to form a polyurethane prepolymer, extending the chain with the modified monomer and castor oil, and finally capping with KH550 to obtain a modified resin.

[0014] Castor oil is added during the preparation of the modified resin, so that the modified resin forms a branched structure. The molecular structure contains silicone segments, cyano groups, benzene rings and long-chain alkyl groups. The benzene ring structure has a stable π electron cloud and is not easy to interact with oil molecules. The long-chain alkyl group and silicone segment can increase the hydrophobicity of the material, thereby improving its oil resistance. The cyano group can give the modified resin a strong polarity, further improving the oil resistance. After extrusion, cold water immersion and ultraviolet light irradiation treatment can form a silicone coating on the surface of the silicone resin, and at the same time form a long-chain fluorocarbon and long-chain alkyl protective layer, thereby preventing water, oil and corrosive substances from contacting the modified resin. The addition of modified fiber filaments can improve the integrity of the material, reduce the diffusion of corrosive media, and at the same time increase the cross-linking density, so that the corrosion resistance, oil resistance and water resistance are further improved. DETAILED DESCRIPTION

[0015] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0016] Example 1 A method for preparing a corrosion-resistant and oil-resistant shore power cable sheath material comprises the following steps: Step A1: 2,2-dihydroxymethylpropionic acid, sodium hydroxide and acetone are mixed evenly, reacted at a speed of 120 r / min and a temperature of 20° C. for 1 h, allyl chloride is added, reacted for 3 h, and the pH is adjusted to be acidic to obtain intermediate 1, intermediate 1, dodecafluoroheptanol, p-toluenesulfonic acid and toluene are mixed evenly, reacted at a speed of 60 r / min and a temperature of 110° C. for 3 h to obtain intermediate 2; Step A2: The intermediate 2, triethoxysilane, chloroplatinic acid and DMF are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 6 hours at a speed of 120 r / min and a temperature of 90° C. to obtain a modified additive; dithioerythritol, dodecyl vinyl ether, benzophenone and DMF are mixed evenly, and the reaction is carried out for 3 hours at a speed of 60 r / min, a temperature of 20° C. and irradiation with 365 nm ultraviolet light; isocyanatepropyl triethoxysilane is added, and the reaction is continued for 2 hours to obtain a strengthening agent; Step A3: Mix microcrystalline cellulose and sodium hydroxide solution, react at a speed of 200 r / min and a temperature of 20°C for 1 hour, add allyl chloride and react for 3 hours to obtain modified cellulose, weigh the following raw materials in parts by weight: 80 parts of modified resin, 8 parts of modified additive, 8 parts of reinforcing agent, 5 parts of modified cellulose and 2 parts of benzoin ethyl ether, melt-extrude the raw materials at a temperature of 170°C, cool and soak in water for 1 hour, and irradiate under 365nm ultraviolet light for 8s to obtain a corrosion-resistant and oil-resistant shore power cable sheath material.

[0017] The molar ratio of 2,2-dihydroxymethylpropionic acid, sodium hydroxide and allyl chloride in step A1 is 1:3.1:2, the molar ratio of intermediate 1 and dodecafluoroheptanol is 1:1, and the amount of p-toluenesulfonic acid is 1% of the mass of dodecafluoroheptanol.

[0018] The molar ratio of intermediate 2 and triethoxysilane described in step A2 is 1:2, the amount of chloroplatinic acid used is 1‰ of the mass of triethoxysilane, the molar ratio of dithioerythritol, dodecyl vinyl ether and isocyanatepropyltriethoxysilane is 1:2:2, and the amount of benzophenone used is 5‰ of the mass of dodecyl vinyl ether.

[0019] The amount ratio of microcrystalline cellulose, sodium hydroxide solution and allyl chloride described in step A3 is 2g:30mL:3mL, and the mass fraction of sodium hydroxide solution is 5%.

[0020] The modified resin is prepared by the following steps: Step B1: Tetramethylcyclotetrasiloxane, acrylonitrile, chloroplatinic acid and DMF are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 4 hours at a speed of 200 r / min and a temperature of 75°C to obtain a modifier; octamethylcyclotetrasiloxane, tetramethyltetraphenylcyclotetrasiloxane, a modifier, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 3 hours at a speed of 120 r / min and a temperature of 105°C to obtain dihydrogenpolysiloxane; Step B2: Dihydrogen polysiloxane, p-hydroxycinnamic acid, chloroplatinic acid and DMF are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 3 hours at a speed of 120 r / min and a temperature of 80° C. to obtain modified polysiloxane; the modified polysiloxane, dodecanol, p-toluenesulfonic acid and toluene are mixed evenly, and the reaction is carried out for 6 hours at a speed of 60 r / min and a temperature of 110° C. to obtain a modified monomer; Step B3: Add polycaprolactone diol into a reaction kettle, introduce nitrogen protection, stir and add diphenylmethane diisocyanate and dibutyltin dilaurate at a speed of 60r / min and a temperature of 60°C, react for 2h, add modified monomer and castor oil, continue to react for 2h, cool to 35°C, add DMF and KH550, continue to react for 1h, and dry to obtain a modified resin.

[0021] The molar ratio of tetramethylcyclotetrasiloxane and acrylonitrile described in step B1 is 1:4, the amount of chloroplatinic acid used is 1‰ of the mass of acrylonitrile, and the molar ratio of octamethylcyclotetrasiloxane, tetramethyltetraphenylcyclotetrasiloxane, modifier, tetramethylammonium hydroxide and tetramethyldisiloxane is 1.6:0.4:0.4:3:2.

[0022] The molar ratio of dihydrogenpolysiloxane and p-hydroxycinnamic acid in step B2 is 1:2, the amount of chloroplatinic acid is 1‰ of the mass of p-hydroxycinnamic acid, the molar ratio of modified polysiloxane and dodecanol is 1:2, and the amount of p-toluenesulfonic acid is 2% of the mass of dodecanol.

[0023] The molar ratio of the polycaprolactone diol, diphenylmethane diisocyanate, modified monomer, castor oil and KH550 in step B3 is 4.5:10:3:1.5:1, and the molecular weight of the polycaprolactone diol is 2000.

[0024] Example 2 A method for preparing a corrosion-resistant and oil-resistant shore power cable sheath material comprises the following steps: Step A1: 2,2-dihydroxymethylpropionic acid, sodium hydroxide and acetone are mixed evenly, reacted at a speed of 150 r / min and a temperature of 20° C. for 1 h, allyl chloride is added, reacted for 4 h, and the pH is adjusted to be acidic to obtain intermediate 1, intermediate 1, dodecafluoroheptanol, p-toluenesulfonic acid and toluene are mixed evenly, reacted at a speed of 60 r / min and a temperature of 115° C. for 4 h to obtain intermediate 2; Step A2: The intermediate 2, triethoxysilane, chloroplatinic acid and DMF are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 7 hours at a speed of 120 r / min and a temperature of 95° C. to obtain a modified additive; dithioerythritol, dodecyl vinyl ether, benzophenone and DMF are mixed evenly, and the reaction is carried out for 4 hours at a speed of 60 r / min, a temperature of 25° C. and irradiation with 365 nm ultraviolet light; isocyanatepropyl triethoxysilane is added, and the reaction is continued for 3 hours to obtain a strengthening agent; Step A3: Mix microcrystalline cellulose and sodium hydroxide solution, react at a speed of 200 r / min and a temperature of 25°C for 1 hour, add allyl chloride and react for 4 hours to obtain modified cellulose, weigh the following raw materials in parts by weight: 90 parts of modified resin, 9 parts of modified additive, 9 parts of reinforcing agent, 8 parts of modified cellulose and 3 parts of benzoin ethyl ether, melt-extrude the raw materials at a temperature of 175°C, cool and soak in water for 1.5 hours, and irradiate under 365nm ultraviolet light for 9 seconds to obtain a corrosion-resistant and oil-resistant shore power cable sheath material.

[0025] The molar ratio of 2,2-dihydroxymethylpropionic acid, sodium hydroxide and allyl chloride in step A1 is 1:3.1:2, the molar ratio of intermediate 1 and dodecafluoroheptanol is 1:1, and the amount of p-toluenesulfonic acid is 1% of the mass of dodecafluoroheptanol.

[0026] The molar ratio of intermediate 2 and triethoxysilane described in step A2 is 1:2, the amount of chloroplatinic acid used is 1‰ of the mass of triethoxysilane, the molar ratio of dithioerythritol, dodecyl vinyl ether and isocyanatepropyltriethoxysilane is 1:2:2, and the amount of benzophenone used is 5‰ of the mass of dodecyl vinyl ether.

[0027] The amount ratio of microcrystalline cellulose, sodium hydroxide solution and allyl chloride described in step A3 is 2g:30mL:3mL, and the mass fraction of sodium hydroxide solution is 5%.

[0028] The modified resin is prepared by the following steps: Step B1: Tetramethylcyclotetrasiloxane, acrylonitrile, chloroplatinic acid and DMF are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 5 hours at a speed of 200 r / min and a temperature of 80°C to obtain a modifier; octamethylcyclotetrasiloxane, tetramethyltetraphenylcyclotetrasiloxane, a modifier, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 3-5 hours at a speed of 120 r / min and a temperature of 110°C to obtain dihydrogenpolysiloxane; Step B2: Dihydrogen polysiloxane, p-hydroxycinnamic acid, chloroplatinic acid and DMF are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 4 hours at a speed of 120 r / min and a temperature of 85° C. to obtain modified polysiloxane; the modified polysiloxane, dodecanol, p-toluenesulfonic acid and toluene are mixed evenly, and the reaction is carried out for 7 hours at a speed of 60 r / min and a temperature of 115° C. to obtain a modified monomer; Step B3: Add polycaprolactone diol into a reaction kettle, introduce nitrogen protection, stir and add diphenylmethane diisocyanate and dibutyltin dilaurate at a speed of 80r / min and a temperature of 60°C, react for 2h, add modified monomer and castor oil, continue to react for 3h, cool to 35°C, add DMF and KH550, continue to react for 1.5h, and dry to obtain a modified resin.

[0029] The molar ratio of tetramethylcyclotetrasiloxane and acrylonitrile described in step B1 is 1:4, the amount of chloroplatinic acid used is 1‰ of the mass of acrylonitrile, and the molar ratio of octamethylcyclotetrasiloxane, tetramethyltetraphenylcyclotetrasiloxane, modifier, tetramethylammonium hydroxide and tetramethyldisiloxane is 1.6:0.4:0.4:3:2.

[0030] The molar ratio of dihydrogenpolysiloxane and p-hydroxycinnamic acid in step B2 is 1:2, the amount of chloroplatinic acid is 1‰ of the mass of p-hydroxycinnamic acid, the molar ratio of modified polysiloxane and dodecanol is 1:2, and the amount of p-toluenesulfonic acid is 2% of the mass of dodecanol.

[0031] The molar ratio of the polycaprolactone diol, diphenylmethane diisocyanate, modified monomer, castor oil and KH550 in step B3 is 4.5:10:3:1.5:1, and the molecular weight of the polycaprolactone diol is 2000.

[0032] Example 3 A method for preparing a corrosion-resistant and oil-resistant shore power cable sheath material comprises the following steps: Step A1: 2,2-dihydroxymethylpropionic acid, sodium hydroxide and acetone are mixed evenly, reacted at a speed of 150 r / min and a temperature of 25° C. for 1.5 h, allyl chloride is added, reacted for 5 h, and the pH is adjusted to be acidic to obtain intermediate 1, intermediate 1, dodecafluoroheptanol, p-toluenesulfonic acid and toluene are mixed evenly, reacted at a speed of 80 r / min and a temperature of 120° C. for 5 h to obtain intermediate 2; Step A2: The intermediate 2, triethoxysilane, chloroplatinic acid and DMF were mixed evenly, nitrogen was introduced for protection, and the reaction was carried out for 8 hours at a speed of 150 r / min and a temperature of 100° C. to obtain a modified additive; dithioerythritol, dodecyl vinyl ether, benzophenone and DMF were mixed evenly, and the reaction was carried out for 5 hours at a speed of 80 r / min, a temperature of 25° C. and irradiation with 365 nm ultraviolet light; isocyanatepropyl triethoxysilane was added, and the reaction was continued for 4 hours to obtain a strengthening agent; Step A3: Mix microcrystalline cellulose and sodium hydroxide solution, react for 1.5 hours at a speed of 300 r / min and a temperature of 25°C, add allyl chloride, and react for 5 hours to obtain modified cellulose. Weigh the following raw materials in parts by weight: 100 parts of modified resin, 10 parts of modified additive, 10 parts of reinforcing agent, 10 parts of modified cellulose and 5 parts of benzoin ethyl ether, melt-extrude the raw materials at a temperature of 180°C, cool and soak in water for 1.5 hours, and irradiate under 365nm ultraviolet light for 10 seconds to obtain a corrosion-resistant and oil-resistant shore power cable sheath material.

[0033] The molar ratio of 2,2-dihydroxymethylpropionic acid, sodium hydroxide and allyl chloride in step A1 is 1:3.1:2, the molar ratio of intermediate 1 and dodecafluoroheptanol is 1:1, and the amount of p-toluenesulfonic acid is 1% of the mass of dodecafluoroheptanol.

[0034] The molar ratio of intermediate 2 and triethoxysilane described in step A2 is 1:2, the amount of chloroplatinic acid used is 1‰ of the mass of triethoxysilane, the molar ratio of dithioerythritol, dodecyl vinyl ether and isocyanatepropyltriethoxysilane is 1:2:2, and the amount of benzophenone used is 5‰ of the mass of dodecyl vinyl ether.

[0035] The amount ratio of microcrystalline cellulose, sodium hydroxide solution and allyl chloride described in step A3 is 2g:30mL:3mL, and the mass fraction of sodium hydroxide solution is 5%.

[0036] The modified resin is prepared by the following steps: Step B1: Tetramethylcyclotetrasiloxane, acrylonitrile, chloroplatinic acid and DMF are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 6 hours at a speed of 300 r / min and a temperature of 80° C. to obtain a modifier; octamethylcyclotetrasiloxane, tetramethyltetraphenylcyclotetrasiloxane, a modifier, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 5 hours at a speed of 150 r / min and a temperature of 110° C. to obtain dihydrogenpolysiloxane; Step B2: Dihydrogen polysiloxane, p-hydroxycinnamic acid, chloroplatinic acid and DMF are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 5 hours at a speed of 150 r / min and a temperature of 85° C. to obtain modified polysiloxane; modified polysiloxane, dodecanol, p-toluenesulfonic acid and toluene are mixed evenly, and the reaction is carried out for 8 hours at a speed of 80 r / min and a temperature of 120° C. to obtain a modified monomer; Step B3: Add polycaprolactone diol into a reaction kettle, introduce nitrogen protection, stir and add diphenylmethane diisocyanate and dibutyltin dilaurate at a speed of 80r / min and a temperature of 65°C, react for 3 hours, add modified monomer and castor oil, continue to react for 3 hours, cool to 40°C, add DMF and KH550, continue to react for 1.5 hours, and dry to obtain a modified resin.

[0037] The molar ratio of tetramethylcyclotetrasiloxane and acrylonitrile described in step B1 is 1:4, the amount of chloroplatinic acid used is 1‰ of the mass of acrylonitrile, and the molar ratio of octamethylcyclotetrasiloxane, tetramethyltetraphenylcyclotetrasiloxane, modifier, tetramethylammonium hydroxide and tetramethyldisiloxane is 1.6:0.4:0.4:3:2.

[0038] The molar ratio of dihydrogenpolysiloxane and p-hydroxycinnamic acid in step B2 is 1:2, the amount of chloroplatinic acid is 1‰ of the mass of p-hydroxycinnamic acid, the molar ratio of modified polysiloxane and dodecanol is 1:2, and the amount of p-toluenesulfonic acid is 2% of the mass of dodecanol.

[0039] The molar ratio of the polycaprolactone diol, diphenylmethane diisocyanate, modified monomer, castor oil and KH550 in step B3 is 4.5:10:3:1.5:1, and the molecular weight of the polycaprolactone diol is 2000.

[0040] Comparative Example 1 Compared with Example 1, no modifying additive was added in this comparative example, and the remaining steps were the same.

[0041] Comparative Example 2 Compared with Example 1, no reinforcing agent was added in this comparative example, and the remaining steps were the same.

[0042] Comparative Example 3 Compared with Example 1, this comparative example did not add modified cellulose, and the remaining steps were the same.

[0043] Comparative Example 4 Compared with Example 1, castor oil was not added in this comparative example, and the remaining steps were the same.

[0044] Comparative Example 5 Compared with Example 1, this comparative example uses ethylenediamine monomer to modify the monomer, and the other steps are the same.

[0045] The materials obtained in Examples 1-3 and Comparative Examples 1-5 were made into specimens of 25 mm × 4 mm × 2 mm, and the tensile strength was tested at a tensile rate of 200 mm / min. They were immersed in 15% by mass acetic acid solution, 15% by mass sodium hydroxide solution, 15% by mass sodium chloride solution and IRM903 oil at a temperature of 25°C for 96 hours, and the tensile strength was tested. The decrease rate of the tensile strength was calculated, and the results are shown in the following table.

[0046]

[0047] It can be seen from the above table that the present invention has good corrosion resistance and oil resistance.

[0048] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a corrosion-resistant and oil-resistant shore power cable sheath material, characterized in that: The specific steps include: Step A1: 2,2-dihydroxymethylpropionic acid, sodium hydroxide and acetone are mixed for reaction, allyl chloride is added, and the reaction is carried out for 3-5 hours, and the pH is adjusted to be acidic to obtain intermediate 1, and intermediate 1, dodecafluoroheptanol, p-toluenesulfonic acid and toluene are mixed for reaction to obtain intermediate 2; Step A2: The intermediate 2, triethoxysilane, chloroplatinic acid and DMF are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out to obtain a modified additive; dithioerythritol, dodecyl vinyl ether, benzophenone and DMF are mixed for reaction, isocyanatepropyl triethoxysilane is added, and the reaction is continued to obtain a strengthening agent; Step A3: After the microcrystalline cellulose and the sodium hydroxide solution are mixed and reacted, allyl chloride is added and the reaction is continued to obtain modified cellulose. The following raw materials are weighed in parts by weight: 80-100 parts of modified resin, 8-10 parts of modified additive, 8-10 parts of reinforcing agent, 5-10 parts of modified cellulose and 2-5 parts of benzoin ethyl ether. The raw materials are melt-extruded at a temperature of 170-180° C., cooled and soaked in water, and then irradiated with ultraviolet light to obtain a corrosion-resistant and oil-resistant shore power cable sheath material.

2. The method for preparing a corrosion-resistant and oil-resistant shore power cable sheath material according to claim 1, characterized in that: The molar ratio of 2,2-dihydroxymethylpropionic acid, sodium hydroxide and allyl chloride in step A1 is 1:3.1:2, and the molar ratio of intermediate 1 and dodecafluoroheptanol is 1:

1.

3. The method for preparing a corrosion-resistant and oil-resistant shore power cable sheath material according to claim 1, characterized in that: The molar ratio of intermediate 2 and triethoxysilane described in step A2 is 1:2, and the molar ratio of dithioerythritol, dodecyl vinyl ether and isocyanatepropyltriethoxysilane is 1:2:

2.

4. The method for preparing a corrosion-resistant and oil-resistant shore power cable sheath material according to claim 1, characterized in that: The amount ratio of microcrystalline cellulose, sodium hydroxide solution and allyl chloride described in step A3 is 2g:30mL:3mL.

5. The method for preparing a corrosion-resistant and oil-resistant shore power cable sheath material according to claim 1, characterized in that: The modified resin is prepared by the following steps: Step B1: Tetramethylcyclotetrasiloxane, acrylonitrile, chloroplatinic acid and DMF are uniformly mixed, nitrogen is introduced for protection, and a reaction is carried out to obtain a modifier; octamethylcyclotetrasiloxane, tetramethyltetraphenylcyclotetrasiloxane, a modifier, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and a reaction is carried out to obtain dihydrogenpolysiloxane; Step B2: dihydrogenpolysiloxane, p-hydroxycinnamic acid, chloroplatinic acid and DMF are uniformly mixed, nitrogen is introduced for protection, and a reaction is carried out to obtain a modified polysiloxane; the modified polysiloxane, dodecanol, p-toluenesulfonic acid and toluene are mixed for reaction to obtain a modified monomer; Step B3: Add polycaprolactone diol into a reaction kettle, introduce nitrogen protection, stir and add diphenylmethane diisocyanate and dibutyltin dilaurate, after reaction, add modified monomer and castor oil, continue reaction, cool down, add DMF and KH550, continue reaction, and dry to obtain modified resin.

6. The method for preparing a corrosion-resistant and oil-resistant shore power cable sheath material according to claim 5, characterized in that: The molar ratio of tetramethylcyclotetrasiloxane and acrylonitrile in step B1 is 1:4, and the molar ratio of octamethylcyclotetrasiloxane, tetramethyltetraphenylcyclotetrasiloxane, modifier, tetramethylammonium hydroxide and tetramethyldisiloxane is 1.6:0.4:0.4:3:

2.

7. The method for preparing a corrosion-resistant and oil-resistant shore power cable sheath material according to claim 5, characterized in that: The molar ratio of the dihydrogenpolysiloxane and p-hydroxycinnamic acid in step B2 is 1:2, and the molar ratio of the modified polysiloxane and dodecanol is 1:

2.

8. The method for preparing a corrosion-resistant and oil-resistant shore power cable sheath material according to claim 5, characterized in that: The molar ratio of polycaprolactone diol, diphenylmethane diisocyanate, modified monomer, castor oil and KH550 in step B3 is 4.5:10:3:1.5:

1.

9. A corrosion-resistant and oil-resistant shore power cable sheath material, characterized in that: Prepared according to any one of the preparation methods described in claims 1-8.

Citation Information

Patent Citations

  • Corrosion-resistant power cable and preparation method thereof

    CN118136322A

  • Low-temperature-resistant middle and low voltage power cable and preparation method thereof

    CN118325216A

  • Cable or cable accessory comprising a fire-resistant layer

    US20170345528A1

  • Fire resistant and food safe cable jacket and method

    US20210233683A1